2021
DOI: 10.1177/2473974x211065437
|View full text |Cite
|
Sign up to set email alerts
|

N95 vs Half‐face Respirator Wear in Surgical Trainees: Physiologic and Psychological Effects of Prolonged Use

Abstract: Objectives As specialists of the upper airway, otolaryngologists are at high risk for COVID-19 transmission. N95 and half-face respirator (HFR) masks are commonly worn, each with advantages in functionality and comfort. In this study, physiologic and psychological parameters of prolonged N95 vs HFR wear were compared. Study Design Prospective crossover cohort study. Setting Single academic tertiary care hospital. Methods A prospective crossover cohort study was performed. Healthy otolaryngology trainees and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
5
0
1
Order By: Relevance
“…The adage that 10% of users have claustrophobia has limited empirical support and was disseminated when respirators were more intrusive than the typical FFR. Controlled laboratory research studies of normal volunteers and health professionals have compared FFR's to elastomeric respirators to demonstrate that anxiety in FFR's is much less frequent 72,73 …”
Section: Resultsmentioning
confidence: 99%
“…The adage that 10% of users have claustrophobia has limited empirical support and was disseminated when respirators were more intrusive than the typical FFR. Controlled laboratory research studies of normal volunteers and health professionals have compared FFR's to elastomeric respirators to demonstrate that anxiety in FFR's is much less frequent 72,73 …”
Section: Resultsmentioning
confidence: 99%
“…Masker N95 juga dapat disimpan dan digunakan kembali, asalkan tidak kotor atau tidak ada kontaminasi virus pada masker, tidak kendor, tidak berlubang, dan tidak basah [10]. Di sisi lain, untuk mencegah penyebaran infeksi, petugas kesehatan yang memakai masker N95 dihadapkan pada beberapa tantangan, yaitu: mengalami kesulitan bernapas, tidak nyaman, dehidrasi [11], penurunan konsentrasi oksigen sirkulasi, peningkatan denyut nadi, sensasi sesak napas, pusing [6], sakit kepala [12], kelelahan ekstrem, kelelahan meningkat [13] menurun saturasi oksigen [14] dan resistensi pernapasan [15].…”
Section: Pendahuluanunclassified
“…In addition to its function as self-protection from viruses, bacteria, and dust, masks have several side effects. Several studies have reported that the use of N95 masks can cause excessive fatigue [4], decreased oxygen saturation, anxiety [5], increased pulse rate, shortness of breath, and headaches [6]).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, to prevent the spread of infection, health workers wearing N95 masks are faced with several challenges, namely: experiencing difficulty breathing, discomfort, dehydration [10], decreased circulating oxygen concentration, increased pulse rate, a sensation of shortness of breath, dizziness [6], headache [11], extreme fatigue, increased fatigue [4] decreased oxygen saturation [5] and respiratory resistance [12].…”
Section: Introductionmentioning
confidence: 99%